Replacement income and informal commerce during the COVID-19 pandemic in Huancayo, Peru - Patrick Clark; Aparicio Chanca-Flores; Susan Vincent (Íconos)
This article constitutes an empirical contribution regarding the correlation between economic informality and the COVID-19 pandemic in Peru. Based on interviews with merchants in the informal sector of the city of Huancayo, the pandemic-related impacts are analyzed in relation to income and livelihoods. It is argued that informal employment played an important role in the tragic indicators of public health in the country. The intrinsic flexibility of this type of activities, specifically for walking merchants, and the lack of access to systems and programs of social security were the main reasons that people worked in this sector to replace the income they lost due to confinement. Thus, the notion “replacement of income” in the economy appeared during the pandemic. The heterogeneity among those who carry out informal work, specifically in terms of their access to different resources, enabled such work and enabled some people to control their exposure to the virus. It is concluded that the focus on economic formalization of the last decades of financial liberalization are not considered advantages that informal activities offer in relation to formalization. In fact, informality continues to offer the best opportunity for immediate income and highly flexible options, in particular for adapting to crisis situations like the pandemic.